2005
DOI: 10.3182/20050703-6-cz-1902.00801
|View full text |Cite
|
Sign up to set email alerts
|

Second Order Sliding Mode Control of Coupled Tanks

Abstract: A second order sliding mode control algorithm is presented for robust control of the liquid level in a pair of interconnected tanks. The controller is implemented on a laboratory rig. The implementation results show robustness to parameter variations such as tank area, the admittance coefficients of various pipes, leakage in the tanks and uncertainty in the pump dynamics. The potential of second order sliding modes for multivariable control is demonstrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…When applied sliding surface has a relative degree of 2 against the control input, the 2SMC is directly applied to system input, otherwise, it acts on the control input derivative. Main results available for 1SMC are provided for SISO systems, however, as shown in [15] and [16], it is generally straightforward to extend the results to MIMO systems.…”
Section: Controller Synthesismentioning
confidence: 98%
See 1 more Smart Citation
“…When applied sliding surface has a relative degree of 2 against the control input, the 2SMC is directly applied to system input, otherwise, it acts on the control input derivative. Main results available for 1SMC are provided for SISO systems, however, as shown in [15] and [16], it is generally straightforward to extend the results to MIMO systems.…”
Section: Controller Synthesismentioning
confidence: 98%
“…In fact sliding mode control is known to be a robust control method appropriate for uncertain systems. Theoretical results but also practical design examples shown that high robustness is maintained against various kinds of uncertainties such as exogenous signal and measurement errors [19], [15]. This The purpose of this paper is to show that both first order (FOSM) and second order sliding mode (SOSM) control can be applied for straightforward development of a coordinated ramp metering strategy.…”
Section: Introductionmentioning
confidence: 98%
“…There are a lot of researches on the applications of sliding mode control. Mohammad Khalid [1] uses a second order sliding mode control for a pair of interconnected tanks. Fei Juntao [2] uses online identification to estimate the bound of uncertainties and disturbance ,design a adaptive sliding mode controller for triaxial gyroscope.…”
Section: Introductionmentioning
confidence: 99%